Performance auditing and resilient public sectors in Bangladesh: enhancing accountability amid global uncertainty - Nazamul Hoque; Harun Bal; Mahi Uddin; Abdullahil Mamun (Journal of Public Budgeting, Accounting & Financial Management, 2026)
Purpose This study examines how performance auditing (PA) influences accountability and organisational resilience in Bangladesh's public sector under conditions of increasing global uncertainty. Design/methodology/approach The study adopts an interpretive qualitative design informed by Institutional Theory. Data were collected through 28 semi-structured interviews with civil society representatives, service users, journalists, academics, and retired public officials, complemented by documentary analysis and non-participant observation. Thematic analysis was used to identify institutional pressures, stakeholder mediation processes, and organisational responses to PA. Findings The findings indicate that while PA enhances transparency and formal oversight, its effects are uneven and conditional, often resulting in procedural or symbolic compliance due to political influence, hierarchical administrative structures, weak enforcement, and limited technical capacity. At the same time, PA can contribute to limited and context-dependent forms of organisational adaptation, including improved recognition of institutional vulnerabilities, incremental adjustments to administrative practices, and enhanced coordination with relevant stakeholders. These effects are mediated through a broader accountability ecosystem, in which civil society organisations, journalists, and policy intermediaries interpret and disseminate audit findings, shaping their public visibility and influence. Research limitations/implications The study focuses on a single developing-country context using qualitative methods, which may limit generalisability. Future research could extend the analysis through comparative or longitudinal designs and incorporate perspectives from serving auditors and policymakers. Practical implications The findings suggest that improving audit follow-up, strengthening auditor capacity, enhancing communication of audit findings, engaging external stakeholders, and incrementally incorporating resilience-oriented approaches can improve the effectiveness of PA. Originality/value This study refines existing understandings of PA by showing that its effects are conditional and mediated, producing incremental and context-dependent organisational responses rather than uniform reform. It contributes to Institutional Theory by identifying the mechanisms through which audit practices interact with institutional pressures and stakeholder mediation, linking auditing to bounded resilience-related outcomes in public sector governance.